K-wire Versus Screw Fixation in Displaced Lateral Condyle Fractures of the Humerus in Children: A Multicenter Study of 762 Fractures. Issue 4 (11th April 2023) - Cummings, Jason L.; Schwabe, Maria T.; Rivera, Asdrubal E.; Sanders, Julia; Denning, Jaime R.; Neal, Kevin; Bellaire, Laura L.; Choe, Josh; Gaio, Natalie; Goldstein, Rachel; Crowe, Mary; Hosseinzadeh, Pooya
Abstract : Introduction: Lateral humeral condyle fractures account for 12% to 20% of all distal humerus fractures in the pediatric population. When surgery is indicated, fixation may be achieved with either Kirschner-wires or screws. The literature comparing the outcomes of these 2 different fixation methods is currently limited. The purpose of this study is to compare both the complication and union rates of these 2 forms of operative treatment in a multicenter cohort of children with lateral humeral condyle fractures. Methods: This retrospective study was performed across 6 different institutions. Data were retrospectively collected preoperatively and 6 weeks, 3, 6, and 12 months postoperatively. Patients were divided into 2 cohorts based on the type of initial treatment: K-wire fixation and screw fixation. Statistical comparisons between these 2 cohorts were performed with an alpha of 0.05. Results: There were 762 patients included in this study, 72.6% (n=553) of which were treated with K-wire fixation. The mean duration of immobilization was 5 weeks in both cohorts, and most patients in this study demonstrated radiographic healing by 11 weeks postoperatively, regardless of treatment method. Similar reoperation rates were seen among those treated with K-wires and screws (5.6% vs. 4.3%, P =0.473). Elbow stiffness requiring further intervention with physical therapy was significantly more common in those treated with K-wires compared with children treated with screws (21.2% vs. 13.9%, P =0.023) as was superficial skin infection (3.8% vs. 0%, P =0.002), but there was no significant difference in nonunion rates between the two groups (2.4% vs. 1.3%, P =1.000). Conclusion: We found similar success rates between K-wire and screw fixation in this patient population. Contrary to previous studies, we did not find evidence that treatment with screw fixation decreases the likelihood of experiencing nonunion. However, given the unique complications associated with K-wire fixation, such as elbow stiffness and superficial skin infection, the treatment with screw fixation remains a reasonable alternative to K-wire fixation in these patients. Level of Evidence: Level III—retrospective comparative study